Quebrando as regras: um estudo sobre Testemunhas de Jeová desassociadas - Mendes, Estevam Dedalus Pereira de Aguiar (2012)
Darning the light of Norbert Elias theory on groups established and outsiders, the sociology of deviance by Howard Becker and studies of social stigma Goffman - This paper analyzes the process of diversion, stigma and social exclusion among Jehovah's Witnesses. Also notes how the belief in the virtue and moral superiority of this religious group is fundamental to the cohesion and submission to the rules established by it. Thus, points out that feelings of shame and guilt, imposed by social exclusion, would boost the return of some church disfellowshipped. The fact that they are generally isolated would therefore be another reason for its weakness as a group, as well as create a stigmatized self-image. Furthermore, evidence shows that new communication technologies, made possible by the internet, this has decreased the size and isolation distance between them which reinforces elisiana idea that the balance of power is not static.